Metalloprotease SPRTN/DVC1 Orchestrates Replication-Coupled DNA-Protein Crosslink Repair - Vaz, Bruno; Popovic, Marta; Newman, Joseph A; Fielden, John; Aitkenhead, Hazel; Halder, Swagata; Singh, Abhay Narayan; Vendrell, Iolanda; Fischer, Roman; Torrecilla, Ignacio; Drobnitzky, Neele; Freire, Raimundo; et al. (Molecular cell, 2016)
The cytotoxicity of DNA-protein crosslinks (DPCs) is largely ascribed to their ability to block the progression of DNA replication. DPCs frequently occur in cells, either as a consequence of metabolism or exogenous agents, but the mechanism of DPC repair is not completely understood. Here, we characterize SPRTN as a specialized DNA-dependent and DNA replication-coupled metalloprotease for DPC repair. SPRTN cleaves various DNA binding substrates during S-phase progression and thus protects proliferative cells from DPC toxicity. Ruijs-Aalfs syndrome (RJALS) patient cells with monogenic and biallelic mutations in SPRTN are hypersensitive to DPC-inducing agents due to a defect in DNA replication fork progression and the inability to eliminate DPCs. We propose that SPRTN protease represents a specialized DNA replication-coupled DPC repair pathway essential for DNA replication progression and genome stability. Defective SPRTN-dependent clearance of DPCs is the molecular mechanism underlying RJALS, and DPCs are contributing to accelerated aging and cancer.